International trade between Spain-Morocco-Portugal: Are there any opportunities for optical products? - Margarita Barrera (Atlantic Review of Economics, 2016)
This paper deals with the international trade interrelations between Spain and its closest neighbours to the South and West: Portugal and Morocco. It analyses the importance of optical products in the trade balance with those countries. To do so, a Social Accounting Matrix for Spain is used as a benchmark economic model, where the optical sector has been disaggregated and international coefficients are considered in order to include the effect of Portugal and Morocco in the Spanish economic system. Results show that, although Portugal plays a considerably important role, there are still growth opportunities toward the relations with Morocco.
Keywords: C67; F59; L6; P45; 330; international trade; optical products; input-output analysis; matrices de contabilidad social